A new species of Peplomicrus Bernhauer from Ecuador (Coleoptera, Staphylinidae, Micropeplinae) - Jałoszyński, Paweł; Sapieja, Mateusz (Zootaxa, 2023)
Peplomicrus nidicola sp. n., a new rove beetle species of the subfamily Micropeplinae is described and illustrated based on a series of males and females collected from nests of New World blackbirds (Icteridae) in northern Ecuador. It is the eleventh nominal species of this genus and the eighth known to occur in the Neotropical realm. A modification of Campbell’s key to the Neotropical species of Peplomicrus Bernhauer is given to include P. nidicola, as well as a list of co-occurring coleopterofauna.